A case report and literature review: gastric cancer with Krukenberg tumor in a patient with situs inversus totalis - Jin, Xiaoli; Shen, Jiankang; Zhou, Ru; Shen, Dongjie; Yuan, Jianming (Frontiers in Oncology, 2025)
The primary modes of metastasis of gastric cancer are through the bloodstream and lymph nodes. However, in cases such as the Krukenberg tumor (KT), gastric cancer cells can spread to organs within the abdominal cavity and develop implantation metastases. This report describes the treatment process for a patient with situs inversus totalis (SIT), gastric cancer, and a KT. A 63-year-old woman with SIT presented with abnormal vaginal bleeding and was diagnosed with gastric cancer with KT. After careful evaluation, the patient underwent total gastrectomy (Roux-en-Y esophagojejunostomy, antecolic, and D2 lymph node dissection), total hysterectomy plus double adnexectomy, and appendectomy. Considering the patient’s SIT, we devised a modified surgical strategy. The surgery was successful. Postoperative adjuvant chemotherapy was administered, and her current evaluation indicated stable disease. Although gastric cancer complicated by KT is rare, it occurs in some cases. Surgical treatment should be considered if both the primary and secondary lesions can be radically resected and supplemented with systemic chemotherapy. For patients with SIT, the surgical approach should be appropriately adjusted with careful preoperative evaluation to ensure procedural safety.